Work-Life Challenges and How to Overcome: An Explorative Study among Female Criminal Investigators - Harularasan, Krishnan; Ida Juliana, Hutasuhut; Mohamad Hardyman, Barawi; Ros Azura, Zahit (UNIMAS Publisher, 2025)
This study explores the significant challenges faced by female investigators in the Criminal Investigation Department (CID), focusing on the complexities of balancing professional duties and family life. The nature of their work, coupled with irregular hours, makes achieving work-life balance particularly difficult. The research, conducted in Malaysia, aimed to identify the work-life challenges, their impacts, and potential solutions to improve the situation for female investigators. Seven female participants, selected through purposive sampling, were interviewed using semi-structured questions. The criteria for selection included a minimum of one year of marriage (with or without children) and at least two years of experience in the CID. Content analysis revealed several challenges, including time constraints, heavy workloads, role conflict, inadequate working facilities, health issues, and long work-home distances. These factors contribute to work-life conflict, highlighting the need for improved time management, stress management, work policies, workplace environment, and enhanced family support.